Contextualization of Ushul Fiqh in Muamalah and Modern Banking: Sharia Solutions in the Global Economic System - Putro, Dimas Handoyo; Nurwahidin; Hannase, Mulawarman; Nafis, Muhammad Cholil; Nur Fatwa; Muttaqin, Mohammad Izdiyan (International Journal of Integrative Sciences, 2024)
This study examines the application of ushul fiqh, the foundational discipline of Islamic jurisprudence, in modern Islamic banking and its implications for the global economic system. Using a Systematic Literature Review (SLR) methodology, this research analyzes academic contributions from 2018 to 2024, focusing on the integration of Islamic principles into banking practices. The findings reveal that ushul fiqh significantly reduces financial instability through principles like the prohibition of riba (interest), reduction of gharar (uncertainty), and emphasis on maslahat (public welfare). These principles align economic transactions with ethical values, fostering inclusivity and sustainability. However, challenges such as regulatory standardization and integration into global markets persist. Despite these, the study identifies substantial growth opportunities for Islamic banking, especially with the rise of sharia-compliant Fintech solutions. This research highlights the potential of ushul fiqh as a transformative tool for promoting justice and resilience in global financial systems while meeting the ethical demands of modern economies